2017
DOI: 10.1038/ncomms15840
|View full text |Cite|
|
Sign up to set email alerts
|

Insufficient antibody validation challenges oestrogen receptor beta research

Abstract: The discovery of oestrogen receptor b (ERb/ESR2) was a landmark discovery. Its reported expression and homology with breast cancer pharmacological target ERa (ESR1) raised hopes for improved endocrine therapies. After 20 years of intense research, this has not materialized. We here perform a rigorous validation of 13 anti-ERb antibodies, using well-characterized controls and a panel of validation methods. We conclude that only one antibody, the rarely used monoclonal PPZ0506, specifically targets ERb in immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
201
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 188 publications
(219 citation statements)
references
References 67 publications
(76 reference statements)
5
201
0
1
Order By: Relevance
“…Additionally, antibodies used for measuring sex hormone receptors varied in quality and some of them led to errors, such as recent evidence for anti-ERβ antibodies [70] and previous evidence of upper non-specific bands from anti-ERα antibodies (HC-20 from Santa Cruz Bio). To improve the quality for the studies of sexual dimorphism in human cancers, genetic assays using tissue-specific knockout mouse models of sex hormone receptors and using human cancer cells with CRISPR/Cas9-mediated manipulations of sex hormone receptor expression will provide more solid and direct answers for this topic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, antibodies used for measuring sex hormone receptors varied in quality and some of them led to errors, such as recent evidence for anti-ERβ antibodies [70] and previous evidence of upper non-specific bands from anti-ERα antibodies (HC-20 from Santa Cruz Bio). To improve the quality for the studies of sexual dimorphism in human cancers, genetic assays using tissue-specific knockout mouse models of sex hormone receptors and using human cancer cells with CRISPR/Cas9-mediated manipulations of sex hormone receptor expression will provide more solid and direct answers for this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Although estrogen was found to promote the growth of urothelial bladder cancer cells through both ERα and ERβ [65, 66], both estrogen therapy and anti-estrogen therapy prevented or suppressed the tumorigenesis of urothelial bladder cancer [6769]. Also, following an antibody validation study, the expression of ERβ in the bladder or bladder cancer cells is debated [70]. Conversely, GPER1-mediated estrogen signaling inhibited the proliferation of urinary bladder cancer cells [71].…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…A prime example of the cost of mistakes in antibody validation can be found in a 2017 study, which suggested that two decades of research attempting to target an estrogen receptor for breast cancer treatment had been wasted owing to insufficiently validated antibodies that were not appropriate for the target in the original paper [7]. Overall, however, the problems facing antibody research have a variety of potential sources.…”
Section: Even Stars Have Their Flawsmentioning
confidence: 99%
“…The three sites mentioned rank by citations or reviews and complement Biocompare and Select Science which I believe rank on a financial basis. I am also not aware of how UniProt and NCBI can be used as antibody search engines so some explanation might be helpful.It is not true that all monoclonal antibodies are highly specific (Page 2), a recent study showed this for antibodies against the oestrogen receptor 1 .Recombinant monoclonals can potentially show batch-to-batch variability caused by changes in the manufacturing process, so I think it is more accurate to say that they should have the least batch-to-batch variability, rather than saying “removing any batch to batch variability” (Page 3).I think the authors are right to the stress the need to select antibodies, where possible, that have been validated for the application of interest (Page 3; final paragraph). I wonder if the authors could also make more of the need to try and find antibodies validated for the tissue and cell type of interest?…”
mentioning
confidence: 99%
“…It is not true that all monoclonal antibodies are highly specific (Page 2), a recent study showed this for antibodies against the oestrogen receptor 1 .…”
mentioning
confidence: 99%